Pemrosesan Query Pada Sistem Monitoring Lingkungan Berbasis Jaringan Sensor Nirkabel - Gunawan Halim; Mohammad Fajar; Abdul Munir (Jurnal Ilmiah Sistem Informasi dan Teknik Informatika (JISTI), 2026)
In wireless sensor network (WSN) and Internet of Things (IoT) systems, inter-node communication is predominantly unidirectional, in which sensor nodes transmit data to a central collection node. Nevertheless, certain scenarios necessitate bidirectional communication, enabling users to request specific data from distributed nodes without reliance on scheduled transmissions. The objective of this study is to develop a data query processing mechanism suitable for environmental monitoring systems based on WSN and IoT architectures. Arduino microcontrollers and the nRF24L01 communication module were utilized as a cost-effective and reliable prototyping platform, with eleven distinct query types designed to facilitate user interaction. Field experiments conducted in an agricultural setting revealed that the query processing system achieved a satisfactory accuracy rate at a sensor-to-base-station distance of 30 meters—specifically, 4 out of 50 transmitted queries failed, resulting in an accuracy of 92%. At a distance of 60 meters, an accuracy rate of 80% was deemed acceptable. Moreover, a numerical simulation model indicated that distances of up to 70 meters constitute the optimal operational range, affording both robust communication accuracy and enhanced energy efficiency. Distances exceeding 70 meters necessitate supplementary strategies, such as the deployment of repeater nodes.